Disengagement from Service in Nigerian Employment Law: An Overview - Anita Nnenna Oteh; Godwin Orakpowenri Orovwiroro (MultiTech Publisher, 2024)
Termination abrogates or brings to an end a valid contract of employment. The act could be in form of notice of intention to bring the agreement between the parties to an end by employer or employee or it could manifest in the form of payment of salary in advance, i.e. in lieu of notice. Dismissal is instant removal from office without notice. Any employer need not adduce reason or motive for terminating the appointment of the employee with notice, but it is mandatory for the said employer to do so where he seeks to dismiss an employee. Dismissal must be based on cogent and compelling grounds as it carries with it the elements of shame, disgrace and odium as well as loss of earnings like wages and other benefits e.g. pension and gratuity. It is an affront to human dignity when one reads such dicta as ‘reinstatement will not be order even if the employee’s right to fair hearing is breached, ‘no employee can be imposed on an unwilling employer even where the employer’s behavior or motive for getting rid of the employee is wrongful, unjustifiable, unfounded or repulsive. Wrongful termination of employment, no matter how grievous can only result in damages. Nigerian employees need to be protected from the victimization, vindictiveness, nepotism and narrow-mindedness of the employers. Justice requires that punishment should be commensurate with the degree of wrongdoing.